Numerical modelling of crural fascia mechanical interaction with muscular compartments. (May 2015) - Pavan, Piero G; Pachera, Paola; Natali, Arturo N
The interaction of the crural fascia with muscular compartments and surrounding tissues can be at the origin of different pathologies, such as compartment syndrome. This pathology consists in the onset of excessive intracompartmental pressure, which can have serious consequences for the patient, compromising blood circulation. The investigation of compartment syndrome etiology also takes into account the alteration of crural fascia mechanical properties as a cause of the syndrome, where the fascial stiffening would result in the rise of intracompartmental pressure. This work presents a computational approach toward evaluating some biomechanical aspects of the problem, within the context of a more global viewpoint. Finite element analyses of the interaction phenomena of the crural fascia with adjacent regions are reported here. This study includes the effects of a fascial stiffness increase along the proximal–distal direction and their possible clinical implications. Furthermore, the relationship between different pre-strain levels of the crural fascia in the proximal–distal direction and the rise of internal pressure in muscular compartments are considered. The numerical analyses can clarify which aspects could be directly implied in the rise of compartment syndrome, leading to greater insight into muscle-fascia mechanical phenomena, as well as promoting experimental investigation and clinical analysis of the syndrome.